Gender Differences in the Use of Complementary and Alternative Medicine and Their Association With Moderate Mental Distress in U.S. Adults With Migraines/Severe Headaches. Issue 1 (25th November 2016) - Rhee, Taeho Greg; Harris, Ila M.
Abstract : Objective: We examined whether the prevalence of complementary and alternative medicine (CAM) use varies by gender, and assessed the interaction of gender and CAM use on moderate mental distress (MMD) in U.S. adults with migraines/severe headaches. Methods: We used data from the 2012 National Health Interview Survey, which represents non‐institutionalized U.S. adults with migraines/severe headaches (n = 4645 unweighted). Using a cross‐sectional design with survey sampling techniques, we conducted descriptive analyses for prevalence of CAM use by gender. Multivariate logistic regression analyses were run to investigate potential roles of migraines/severe headaches and CAM use on MMD by gender. Results: The overall prevalence of past year CAM use was 44.4%. Women consistently used CAM more frequently than men ( P  = .004). The most commonly used CAM types included herbal supplements (22.2%), massage (14.2%), and chiropractic/osteopathic (13.9%). After controlling for covariates, the odds of MDD were increased by the presence of migraines/severe headaches ( P  < .001) and the use of any CAM ( P  < .001). The interaction effect of migraines/severe headaches and CAM use decreased the odds of MMD by 27% in women ( P  < .05), but not in men. Conclusion: Women used CAM more frequently than men among adults with migraines/severe headaches in the United States. In addition, the interaction of gender and CAM use exists; the CAM use was associated with decreased odds of MMD among women only, suggesting that women with migraines/severe headaches may have benefited from CAM for their mental distress. Future research is needed to explore why such patterns vary by gender.